Tetranuclear Copper(II) Complexes with Macrocyclic and Open‐Chain Disiloxane Ligands as Catalyst Precursors for Hydrocarboxylation and Oxidation of Alkanes and 1‐Phenylethanol. Issue 29 (18th August 2014) - Zaltariov, Mirela‐Fernanda; Alexandru, Mihaela; Cazacu, Maria; Shova, Sergiu; Novitchi, Ghenadie; Train, Cyrille; Dobrov, Anatolie; Kirillova, Marina V.; Alegria, Elisabete C. B. A.; Pombeiro, Armando J. L.; Arion, Vladimir B.
Abstract: Two new tetranuclear copper(II) complexes [Cu4 (μ4 ‐O)(L 1 )Cl4 ] (1 ) and [Cu4 (μ4 ‐O)(L 2 )2 Cl4 ] (2 ), whereH2 L 1 is a macrocyclic ligand resulting from [2+2] condensation of 2, 6‐diformyl‐4‐methylphenol (DFF) and 1, 3‐bis(aminopropyl)tetramethyldisiloxane, andHL 2 is a 1:2 condensation product of DFF with trimethylsilyl p ‐aminobenzoate, have been prepared. The structures of the products were established by X‐ray diffraction. The complexes have been characterised by FTIR, UV/Vis spectroscopy, ESI mass‐spectrometry and magnetic susceptibility measurements. The latter revealed that the tetranuclear complexes can be described as two ferromagnetically coupled dinuclear units, in which the two copper(II) ions interact antiferromagnetically. The compounds act as homogeneous catalyst precursors for a number of single‐pot reactions, including (i) hydrocarboxylation, with CO, H2 O and K2 S2 O8, of a variety of linear and cyclic( n = 5–8) alkanes into the corresponding C n +1 carboxylic acids, (ii) peroxidative oxidation of cyclohexane, and (iii) solvent‐free microwave‐assisted oxidation of 1‐phenylethanol. Abstract : Two new tetranuclear copper(II) complexes act as homogeneous catalyst precursors for the single‐pot hydrocarboxylation of a variety of linear and cyclic C n ( n = 5–8) alkanes into the corresponding C n +1 carboxylic acids, peroxidative oxidation of cyclohexane, and solvent‐free microwave‐assisted oxidation of 1‐phenylethanol.